Enhancing Performance of Small and Medium Enterprises (SMEs) through Supply Chain Integration - An Examination of the Fisheries Sector in Aceh - Rizki Agam Syahputra; Muhammad Reza Aulia; Yulia Annisa; Iing Pamungkas; Adib Adib (xxxx-xxxx, 2023)
This article proposes an qualitative approach to determine the underlying dimensions of Supply Chain Management integration and its relation to performance among small firm in Aceh, Indonesia  with special emphasis on the tuna industry.. The overall aim of the study is to better understand successful SCM practices which have been implemented by small industry in Aceh and the challenges faced in the process. This paper uses qualitative data, which was collected from open-ended interviews with stakeholders in a leading Aceh tuna business, together with the SCOR model, which is used to define supply chain processes and associated key performance indicators (KPI). The result of this research indicates that the industry regards flexibility, efficiency, and quality as the most important indicators in their supply chain operation. however, factors such as financial, SCM expertise, infrastructure and resource create a barrier in implementing an effective supply chain. Further to this, Successful SCM strategies improving SCM performance were identified based on each performance indicators. The result of this paper is expected to contribute to theoretical and practical knowledge of SCM practice, and to develop recommendation for future development of industry with small-scale capabilities.